Efecto de la aireación nocturna en el almacenamiento de maíz. (1978)
An experiment was conducted to determine the effectiveness of the overnight aireation on shelid corn, under conditions of low level aireation and 100 of relative humidity. The study took place a three different ICA's Experimental Stations, namely: Tibaitatd (2.550 m.a.s.l.), Palmira (1.006 m.a.s.l.) and Turipaná (12 m.a.s.I.). Mean annual overnight temperatures are respectively: 6.80 C. 18.50 1 0 C and _1 C. Readings of temperature, determinations of grain moisture, and observations of damage in grains were made at various layets of each silo. Results showed low temperatures and high moisture at the lower layers of the silo, while completely opposite condition were encountered at the top layers. During aireation, damage of grains remained constant and the number of insects decreased.